Poisonous Animals (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Nature is home to millions of animal species, some of which have special mechanisms for self-defense or prey capture. One such mechanism is the production of venom. Although venomous animals can be dangerous to humans, they are important in maintaining biodiversity and ecological balance. Toxins from venomous animals are used in medicine to combat and protect against various diseases.